Desenvolvimento de uma formulação pediátrica anti-helmíntica: Supositório contendo extrato de Operculina macrocarpa - Duarte, Allana Brunna Sucupira (2017)
Intestinal parasites caused by helminths are among the most frequent public health problems and affect mainly children. Conventional treatment of such diseases is carried out with antiparasitics having various adverse effects and are available in the dosage forms of tablets, syrups and suspensions which have disadvantages in pediatric use such as inability to swallow and unpleasant taste. Among the various forms of treatment, phytotherapy has been highlighted by the use of medicinal plants as an excellent alternative for the treatment of helminthes. In this way, this study proposed to obtain a formulation in the form of suppository containing nebulized extract of the tuber Operculina macrocarpa. Eighty-one extracts were produced using different extraction techniques, hydroalcoholic concentrations and quantities of plant material, following a Factorial Planning 3^3 , in order to determine the best yield extract. All extracts were characterized for their composition of polyphenols, condensed tannins and flavonoids. The extract with the highest amount of phytochemicals was selected for the other studies and development of the formulation, since there was no statistical difference in relation to yield. Thus, the extract produced by maceration was selected using 10 g of vegetal material dissolved in 100 mL of 50% (v/v) ethanol/water solution. The extract did not present cytotoxicity in erythrocytes. The anti-helminth activity test performed in goats showed that 14 days after treatment administration there was a reduction in the mean number of eggs per gram of faeces (OPG) of 79,40% compared to day zero. Thermal data demonstrated that the pharmaceutical excipients cocoa butter, EDTA and the mixture of methylparaben and propylparaben did not present incompatibility with the O.macrocarpa nebulizer extract and its binary mixtures, and these were therefore selected for the manipulation of suppositories. Therefore, the proposed anti-helminthic pediatric formulation was successfully obtained and had adequate organoleptic characteristics, average weight and disintegration time.